Pneumococcal Pneumonia: Mechanisms of Infection and Resolution - Dockrell, David H. (American College of Chest Physicians, 2012)
Vaccination and antimicrobial therapy remain the cornerstones of the management of pneumococcal pneumonia. Despite significant successes, the capacity of the pneumococcus to evolve in the face of the selective pressure of anticapsular immunity challenges immunization programs. Treatment focuses on antimicrobial therapy but ignores the central role of the dysregulated inflammatory response during pneumonia. Future therapeutic approaches need to build on the considerable recent advances in our understanding of the pathogenesis of pneumococcal pneumonia, including those from models of pneumonia. Enhancement of the essential components of the host response that prevents most colonized individuals from developing pneumonia and strategies to limit inappropriate inflammatory responses to lower respiratory tract infection are approaches that could be exploited to improve disease outcome. This review highlights recent discoveries relating to the microbial and host determinants of microbial clearance and regulation of the inflammatory response, which provide clues as to how this could be achieved in the future.